Analysis for Variation Characteristics and Trends of Runoff and Sediment in Nandu River - LIN Youwen; YU Miao; ZHU Lirong; YE Changqing; HUANG Junlin (Renmin Zhujiang)
As the significant changes of both runoff and sediment content in many rivers in the changing environment,it's practical to analyze the variation characteristics and trends of runoff and sediment for predicting hydrologic situation exactly and identifying the influence mechanism effectively.Based on the data from the Santan Hydrological Station and Longtang Hydrological Station in Nandu River,this paper analyzes the variation characteristics and trends of runoff and sediment in Nandu River by mathematical statistical methods such as correlation analysis and trend analysis.The results show that:There is no significant change in total runoff of either Longtang or Santan Station from year to year.However,compared with 1977—1997,the amount of sediment transport at Longtang station decreased significantly from 1998 to 2007,which reduced about 33.82×104 t every year,accounting about 57.61%.The total runoff at Santan Station shows a downward trend,while that at Longtang Station has a slight downward trend.The amount of sediment transport at Santan Station does not change obviously,while that at Longtang Station reduces significantly.In addition,among the factors that affect the variation in runoff and sediment,precipitation is the main reason for the change in runoff,and sediment interception by reservoirs is an important reason for the decrease in sediment transport.